MOLECULAR GENETIC MECHANISMS OF DEVELOPMENT OF CHRONIC VENOUS INSUFFICIENCY (Conferencea, 2024)
The actuality. Chronic venous insufficiency (CVI) is an important medical problem in developed countries. Increased venous pressure in varicose veins (VV) may contribute to the overexpression of certain matrix metalloproteinases (MMPs) that affect the endothelium, smooth muscle and extracellular matrix proteins of the vein wall. Gelatinases, which include MMP-2 (gelatinase A) and MMP-9 (gelatinase B), are responsible for the degradation of the extracellular matrix (ECM) in the vein wall under both physiological and pathological conditions